Education on the role of family in stunting prevention in toddlers - Nordianiwati Nordianiwati; Nur Gilang Fitriana; Lamria Situmeang; Indrawati Aris Tyarini; Ari Setyawati (Journal Pengabdian Masyarakat Politeknik Sandi Karsa, 2024)
Stunting in toddlers is a global health problem that requires serious attention, especially in developing countries. This community service activity aims to examine the role of families in stunting prevention in toddlers, focusing on educational aspects. The family has a significant role in ensuring the optimal growth and development of children. This community service activity is carried out through the planning, implementation, and evaluation stages. The results showed that family education is closely related to stunting prevention, involving understanding nutrition, healthy eating, sanitation, and hygiene practices. Factors such as a family's education level, socioeconomic status, and access to health services affect a family's ability to implement stunting prevention practices. Therefore, appropriate and easily accessible educational programmes need to be developed to increase family knowledge and awareness about the importance of child growth and development. This activity recommends that the government, health institutions, and health practitioners integrate educational approaches into stunting prevention programmes. Collaborative efforts between various parties are needed to create an environment that supports optimal child growth and reduces stunting at the population level.